Jovens rurais de Iracema do Oeste - Junges, Dóris Mariani (2009)
This study indicates the profile of young rural de Iracema do Oeste. The analyzed literature points an immigratory tendency still expressive throughout the world direct to the urban environment and for the inexistence of studies related to those youths who remain in the countryside. The formulation of the research problem based in the reasons of the countryside youths remain. The tested hypothesis in the current study was that the remain of the youths from Iracema do Oeste in the countryside would justify for the access facilities to services once only found in the urban environment. The countryside improvement deriving from the modernization occurred in the last decades, pointed out by the authors in the bibliography review would be amplifying a franchise, opening new possibilities of consumption for the population from the countryside. The rural youths also would not isolate anymore. The means of communication, the transport facilities, the telephony systems and the study conditions would approximate the countryside and the city. Beyond these factors and changings in the countryside, the pluriactivity, synonym of the diversification of the use of the rural space, joined the mentioned changings, could be an alternative of income and the abidance of the youths in the countryside. Nevertheless the raised hypotheses are not confirmed. The obtained replies through questionnaires applied to youths from the countryside from Iracema do Oeste show that the choice for the abidance in the countryside is regulated to a positive evaluation about their own lifestyle, however with the advance of the age and the necessity of having a profession, the choice of leaving the countryside is eminent. The possibility of self income acquiring also did not confirm, even in properties of diversified production. The tendency for the abidance is clearly in the youths from families until four components that possess self property that do not work out of the property without self income and with low level of schooling.